Effects of Sulfur Application on the Quality of Fresh Waxy Maize - Chenyang Jiang; Yuwen Liang; Yuru Wang; Genji You; Jian Guo; Dalei Lu; Guanghao Li (Plants)
Balanced fertilizer application is crucial for achieving high-yield, high-quality, and efficient maize cultivation. Sulfur (S), considered a secondary nutrient, ranks as the fourth most essential plant nutrient after nitrogen (N), phosphorus (P), and potassium (K). S deficiency could significantly influence maize growth and development. Field experiments were conducted in Jiangsu, Yangzhou, China, from April 1 to July 20 in 2023. Jingkenuo2000 (JKN2000) and Suyunuo5 (SYN5) were used as experiment materials, and four treatments were set: no fertilizer application (F0), S fertilizer application (F1), conventional fertilization method (F2), and conventional fertilization method with additional S application (F3). The objective was to investigate the impact of S application on grain weight and the quality of fresh waxy maize flour and starch. The results indicated that all fertilization treatments significantly increased grain weight and the starch and protein contents in grains compared to no fertilization. Among these, F3 exhibited the most significant increases. Specifically, in JKN2000, the grain weight, starch content (SC), and protein content (PC) increased by 27.7%, 4.8%, and 14.8%, respectively, while in SYN5, these parameters increased by 26.3%, 6.2%, and 7.4%, respectively, followed by F2 and F1. Compared to F0, F3 increased starch and protein contents by 4.8% and 14.8% in JKN2000, and by 6.2% and 7.4% in SYN5. Compared to F0, F2 and F3 significantly increased the iodine binding capacity (IBC) of SYN5, with F3 being more effective than F2, while they had no significant effect on the IBC of JKN2000. The peak viscosity (PV) and breakdown viscosity (BD) of waxy maize flour and starch for both varieties showed a consistent response (increasing trend) to S application, and F3 had the largest increase. Regarding the thermal properties of waxy maize flour, F3 significantly enhanced the retrogradation enthalpy (ΔHgel) of both varieties compared to F0, while achieving the lowest retrogradation percentage (%R). In starch, the highest ΔHgel and the lowest %R were observed under the F2 treatment. In summary, under the conditions of this experiment, adding S fertilizer to conventional fertilization not only increased the grain weight of waxy maize but also effectively optimized the pasting and thermal properties of waxy maize flour and starch.